INSTINTO MATERNO? A cristalização da identidade feminina na maternidade - SOUSA, Sofia Ravinny Leal de (2024)
From the 18th century onwards, more specifically in 1760, the encouragement of a new type of relationship between parents and children began to exist, marked by care and affection as we know it today and maternal love and instinct. As the idea of childhood was developed as a stage of special care, the conception of maternal instinct, of the mother's sacrificial love for her children and women began to be valued. In this context, we can see the strong influence of religion, the State and science in the naturalization of motherhood and its conception as instinctive. This master's thesis aimed to investigate how the discourse of naturalization of maternal instinct is constructed and how this phenomenon is still consolidated today and what its function is in the current scenario. Through a qualitative study based on Martín Heidegger's phenomenological analysis, the research sought to understand what current psychology studies investigate regarding the phenomenon of maternal instinct. The investigation included a bibliographical survey of scientific production in psychology, the description and interpretation of the main understandings about the maternal instinct, linked to a phenomenological-existential understanding of the phenomenon in modernity. The results highlighted the lack of articles on the phenomenon in question, highlighting the need to expand the fields of academic research beyond studies focused on understandings arising from the field of natural sciences. To analyze the results, three categories of meaning were constructed: family: indisputable social unit; Normative mothers and the pathologization of the maternal experience; The woman, in her condemnation. The research concluded that the maternal instinct phenomenon has been used as a strategy for social reorganization and control at different times in history. Women's regression to the domestic and the natural takes on new aspects today, although it often announces the same thing: gender roles traditionally fixed in the binary logic of being a man versus being a woman in society.